Importance of dermoscopy in differentiating common urticaria and urticarial vasculitis: A randomized control study - Mahajabeen Saheb Patel Madarkar (Wolters Kluwer Medknow Publications, 2021)
Background: Urticarial vasculitis is a clinicopathological entity that overlaps with common urticaria, and histopathological diagnosis is required for differentiation between them. Objectives: To determine, for the first time, if skin surface microscopy can aid in the clinical differentiation between common urticaria and urticarial vasculitis in daily practice. Materials and Methods: Lesions in 20 patients with a clinical diagnosis of urticaria were studied. All urticarial lesions were subjected to dermoscopy, skin biopsy, and histopathological examination to confirm the diagnosis. Dermoscopy was performed using Derm Lite 3 dermoscope and images captured were anyalysed. Clinical images were taken. A punch biopsy was performed in all patients. Statistical analysis was done. Results: In 11 patients diagnosed clinically as chronic urticaria, on dermoscopy showed red lines in 9(45%), red dots in 2 (10%) and structureless areas in 8(40%) patients. In 9 patients diagnosed as urticarial vasculitis clinically, on dermoscopy revealed purpuric dots in 8(40%) and purpuric globules in 5(25%) patients. Conclusion: We conclude that in our setting dermoscopy significantly facilitates the detection, diagnosis and differentiation of common urticaria and urticarial vasculitis.